Characteristics of a diet and supplementation of American football team players: following a fashionable trend or a balanced diet? - Joanna Smarkusz; Joanna Zapolska; Katarzyna Witczak-Sawczuk; Lucyna Ostrowska (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. American football is based on speed and strength efforts players forming both defensive and offensive units in the team. Players' diet's may differ with regard to the variety of physical efforts performed and their different nutritional needs. Objective. The aim of the study was to evaluate a diet and the supplementation, including the comparison of both the defensive and offensive player's formations, which may constitute a background of sportsmen' balanced menus permitting them to achieve better sports results. Material and methods. The study included 44 American football players (24 defensive, 20 offensive players). The study group completed a three-day-dietary recall containing the time of consumption as well as a questionnaire about a type and amount of supplements used, including questions of one or multiple choice. Results. The mean age of defensive players was 25.1±5.8 years, while of offensive players was 23.4±3.7. The mean body mass equaled 101±15.6 kg vs. 88.7±22.2 kg. The mean height of defensive players was 183.8±6 cm vs. 182.4±7.3 cm of offensive players. Offensive players consumed on average 2471.9±838.6 kcal/24 hs, whilst defensive players 3086.1±908.9 kcal/24 hs. The mean level of cholesterol level consumption equaled 667.81±300 mg in defensive players, while 546.2±285 mg in offensive players. Of energizing preparations, protein powder supplement and coffee were most frequently chosen by players. Conclusions. Defensive unit players were characterized by higher consumption of certain nutritional components and more frequent diet supplementation. A too low caloric intakes well as water, vitamin D, carbohydrates and dietary fiber intake was observed in both units. A high intake of high level cholesterol products requires reduced consumption of saturated fatty acids and increased consumption polyunsaturated fatty acids.